Assembly of the Entire Carbon Backbone of a Stereoisomer of the Antitumor Marine Natural Product Hemicalide. Issue 11 (25th January 2019) - Lecourt, Camille; Dhambri, Sabrina; Yamani, Khalil; Boissonnat, Guillaume; Specklin, Simon; Fleury, Etienne; Hammad, Karim; Auclair, Eric; Sablé, Serge; Grondin, Antonio; Arimondo, Paola B.; Sautel, François; et al.
Abstract: A strategy for the assembly of the entire carbon backbone of a stereoisomer of the antitumor marine natural product hemicalide has been investigated. The devised convergent approach relies on Horner–Wadsworth–Emmons and Julia–Kocienski olefination reactions for the construction of the C6=C7 and C34=C35 double bonds, respectively, an aldol reaction to create the C27−C28 bond, and a Suzuki–Miyaura cross‐coupling as the endgame to form the C15−C16 bond. Abstract : A strategy for the assembly of the entire carbon backbone of a stereoisomer of the antitumor marine natural product hemicalide has been investigated. The devised convergent approach relies on Horner–Wadsworth–Emmons and Julia–Kocienski olefination reactions for the construction of the C6=C7 and C34=C35 bonds, respectively, an aldol reaction to create the C27−C28 bond, and a Suzuki–Miyaura cross‐coupling as the endgame to form the C15−C16 bond.